2018
DOI: 10.1111/bjet.12686
|View full text |Cite
|
Sign up to set email alerts
|

A discursive question: Supporting student‐authored multiple choice questions through peer‐learning software in non‐STEMM disciplines

Abstract: Peer‐learning that engages students in multiple choice question (MCQ) formulation promotes higher task engagement and deeper learning than simply answering MCQ’s in summative assessment. Yet presently, the literature detailing deployments of student‐authored MCQ software is biased towards accounts from Science, Technology, Engineering, Maths and Medicine (STEMM) subjects, rather than discursive subjects or disciplines where content may contain fewer absolute facts and objective metrics and more nuance. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This point is in line with some studies by past researchers such as (Hossain & Sormunen, 2019;Barnard et al, 2019;Arco-Tirado et al, 2020;Chiu & Hew, 2018;Corrégé & Michinov, 2021). Snow et al (2019) explained that peer learning encourages student involvement in completing assignments is higher and obtains deeper learning than just answering questions and allows students to compose, evaluate and comment on questions and answers with friends. Peer learning increases enthusiasm, self-efficacy and readiness among students in addition to improving leadership skills (Lairamore et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This point is in line with some studies by past researchers such as (Hossain & Sormunen, 2019;Barnard et al, 2019;Arco-Tirado et al, 2020;Chiu & Hew, 2018;Corrégé & Michinov, 2021). Snow et al (2019) explained that peer learning encourages student involvement in completing assignments is higher and obtains deeper learning than just answering questions and allows students to compose, evaluate and comment on questions and answers with friends. Peer learning increases enthusiasm, self-efficacy and readiness among students in addition to improving leadership skills (Lairamore et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A common use of question repositories in PeerWise by students is for review and practice purposes leading up to summative tests and exams. Prior work has shown that answering activity in PeerWise typically increases rapidly before a test [38], and that answering questions is strongly predictive of subsequent test performance [39], [40]. Instructors are also able to make use of the questions, for example by reviewing a question repository to identify topics that are challenging for students, or by selecting high-quality questions for use on summative tests and exams.…”
Section: Crowdsourcing Systems a Peerwisementioning
confidence: 99%
“…Collaborative question generation improves self-confidence and critical thinking, sheds light on different ways to solve a problem, supports ideation, exhilarates students, facilitates rapid peer-evaluation, and improves deep learning [64,19,76,25,16,65,14,6,27,47,45,4,8,17,60,49,22]. Creating question stems, correct/wrong choices, and justifications for each choice involves critical thinking and evaluation that result in deep learning [25,49,20].…”
Section: Collaborative Question Generationmentioning
confidence: 99%
“…It provides students with a learning environment where they generate questions and share them with their classmates for self-testing. Questiongeneration through PeerWise is found helpful in a large spectrum of disciplines [64,25]. Replacing weekly course assignments with question generation also showed a significant increase in final exam grades [4].…”
Section: Collaborative Question Generationmentioning
confidence: 99%